Child Health Problems in Agricultural Setting - Lantin Sulistyorini; Peni Perdani Juliningrum; Ira Rahmawati; Eka Afdi (Faculty of Nursing Universitas Padjadjaran, 2020)
Besuki Residency well known at agricultural field. Child and infant mortality in this area is high. Child health problems of agricultural-oriented at Besuki Residency no one has research yet. This research uses quantitative methods that are retrospectives that include child health problems since 2017 until 2018. Quantitative method is used to collect data on patient characteristics (gender, disease, nursing problems, and age criteria) and illness to the children’s disease based on agricultural that arise due to activities or agricultural climate. The sample included 807 children at seven hospital scattered in several residency areas using quota sampling technic. Data analysis uses confirmatory factor analyze (CFA), with parameter data estimation uses analysis of moment structures. The result of p-values for health problems to gender = 0.033 (p<0.05), health problems to disease = 0.008 (p<0.05), health problems to nursing problems = 0.000 (p<0.05), health problems to age criteria = 0.000 (p<0.05). Fit model value indicates that the model is perfect fit. Child health problems, especially such as pneumonia, diarrhea, and malaria in the agricultural area with an agricultural perspective in the Besuki Residency can affect gender, disease, nursing problems, and age criteria. So that these health problems require specific health interventions or programs according to the characteristics of gender, disease, nursing problems, and age criteria. The nurse should have a mapping of nursing problems and special agriculture-oriented interventions.